2011
DOI: 10.1039/c1dt10798d
|View full text |Cite
|
Sign up to set email alerts
|

The P2-Na2/3Co2/3Mn1/3O2 phase: structure, physical properties and electrochemical behavior as positive electrode in sodium battery

Abstract: Manganese substituted sodium cobaltate, Na(2/3)Co(2/3)Mn(1/3)O(2), with a layered hexagonal structure (P2-type) was obtained by a co-precipitation method followed by a heat treatment at 950 °C. Powder X-ray diffraction analysis revealed that the phase is pure in the absence of long-range ordering of Co and Mn ions in the slab or Na(+) and vacancy in the interslab space. The oxidation states of the transition metal ions were studied by magnetic susceptibility measurements, electron paramagnetic resonance (ESR) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

19
186
1
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 233 publications
(208 citation statements)
references
References 22 publications
19
186
1
1
Order By: Relevance
“…Recently, several layered Na x MO 2 (M: 3d transition metals, TMs) compounds have been proposed as positive electrode materials for sodium-ion batteries [42][43][44][45][46][47][48][49][50][51][52] . It has also been demonstrated that P2-type materials show better storage performance than that of O3-type materials (Note that the notations of P2 and O3 were defined by Delmas et al 53 , they refer to different ways of the stacking of the oxygen layer, for example, ABBA for P2, ABCABC for O3 and so on) 46 .…”
mentioning
confidence: 99%
“…Recently, several layered Na x MO 2 (M: 3d transition metals, TMs) compounds have been proposed as positive electrode materials for sodium-ion batteries [42][43][44][45][46][47][48][49][50][51][52] . It has also been demonstrated that P2-type materials show better storage performance than that of O3-type materials (Note that the notations of P2 and O3 were defined by Delmas et al 53 , they refer to different ways of the stacking of the oxygen layer, for example, ABBA for P2, ABCABC for O3 and so on) 46 .…”
mentioning
confidence: 99%
“…By comparing with the spectra of the standard transition metal oxide compounds, it is revealed that the average valence states of the Co, Mn, and Ti ions in the as‐synthesized NCMT‐2 are 2+, 3.7+, and 4+. It is very surprising that Co ions can be stabilized at 2+ in the P2‐type layer‐structured compounds, since the valence state of Co ions in most layer‐structured cathode materials is 3+ 12, 23, 39. In addition, the valence state of Mn ions in NCMT‐2 is 3.7+, which is higher than Mn 3+ in tunnel‐structured Na 0.66 Mn 0.66 Ti 0.34 O 2 18.…”
Section: Resultsmentioning
confidence: 99%
“…Over the past years, various cathode materials have been investigated, including layered oxides,9, 10, 11, 12, 13, 14, 15 tunnel‐structured oxides,16, 17, 18 polyanion compounds,19, 20 and organic compounds 21. Among them, layered oxides are promising cathode materials with a general formula of Na x TMO 2 (TM = transition metals, such as Co, Ni, Mn, Cr, Fe, and Cu),9, 12, 22, 23, 24 which can be categorized into two main groups: P2‐type and O3‐type. P2 and O3 are defined according to the oxygen stacking sequence and coordination environment of the alkali ions 25, 26.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations